Management of the bank's credit activity as a factor of ensuring its stability - Tang Zhiyu (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the processes involved in managing the bank's credit activity. The subject of research encompasses theoretical aspects and practical recommendations for improving the management of credit activities in a banking institution. The purpose of the qualifying master's thesis is to summarize theoretical and methodological aspects and provide recommendations for improving the management of the bank's credit activities. Based on the research results, theoretical and practical provisions have been formulated and translated into specific proposals to enhance the effectiveness of the credit policy formation and implementation at JSC CB PrivatBank. The results obtained can be used to address issues related to the management of credit activities not only in PrivatBank but also in other banking institutions.
Управління кредитною діяльністю банку як фактор забезпечення його стабільності
Scientific adviser: Utenkova Karina, doctor of economics, associate professor, department banking business and financial technologies
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; credit policy; credit portfolio risks; credit policy management